Niacin (vitamin B3) - Fairweather-Tait, Susan (Henry Stewart Talks, 2026)
Functions of niacin in the body, Food sources for niacin, Absorption and metabolism, Deficiency of niacin and pellagra, Dietary reference values for niacin for adults